PERAN DAN DINAMIKA KELEMBAGAAN P3A DALAM PENGELOLAAN AIR SAWAH DI DESA ABBANUANGNGE KECAMATAN PAMMANA KABUPATEN WAJO - Kasim, Erni; Syahrullah, Syahrullah; Murmayani, Murmayani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This research was conducted in Abbanuangnge Village, Pammana District, Wajo Regency, this research started from March 2022 to May 2022. The study population was 141 farmers from one P3A group. The purpose of this study was to determine the role and institutional dynamics of P3A in the management of paddy water in Abbanuangnge Village, Pammana District, Wajo Regency. The method of determining respondents is done by taking 10 members in the group. Data collection techniques are carried out by observation, interviews, and documentation. The results of the study show that the institutional role of P3A Sipakatuwo in the operation and maintenance of irrigation networks and the rehabilitation of irrigation networks has been carried out well. P3A institutions have shown dynamism in rice field water management where this dynamic is related to the existence of objectives, structure, functions, guidance, cohesiveness, atmosphere, and institutional pressure.